Perancangan Bed Table (Baby Tafel) pada Ruang Ganti Bayi Area Mall di Surabaya - Tania Elen Wicita (Intra, 2017)
Baby changing room at mall area in Surabaya is designed to meet the needs of users. Baby tafel in the mall today is not well designed to meet the needs of users. Rapid movement of baby-diaper moms is needed because baby who will switch diapers are active in their movements. The design of a multifunctional Tafel baby can be an answer for parents to make rapid movements in the form of baby diapers in the mall area, so that users can do activities efficiently, practically and comfortably.  Baby Tafel is designed with fun concept, efficient and multifunctional. Existing designs adapted to the concept of cartoonish cartoons are colored according to cartoon concept of zebras, lions, giraffes, elephants, and hippo. The cartoon concept of this animal will directly give the impression cheerful for the child and mother to do diaper change activity.